A Semantics-based visualization building process - Larrea, Martín Leonardo (2010)
A successful visualization allows the user to gain insight into the data in an effective way. Even with today’s visualization systems that give the user a considerable control over the visualization process, it can be difficult to produce an effective visualization. This paper is a step forward to achieve a visualization system that assists the user in the configuration and preparation of the visualization by considering both the semantic of the data and the semantic of the stages, through all the visualization process. In this article we present a system for file hierarchies visualization where the color assignment and the configuration of the visualization technique are carried out by reasoning processes. This work sets the way forward for the integration of reasoning in the visualization process.